Ocular inflammatory effects of intravitreally-injected tumor necrosis factor. - Rosenbaum, J. T. (1988)
Many of the pathophysiologic effects of bacterial endotoxin have recently been attributed to a monokine, tumor necrosis factor (TNF). The rabbit eye is extremely sensitive to locally injected endotoxin. The authors have investigated the possible contribution of TNF to ocular inflammation in a rabbit model. The intravitreal injection of 10(5) to 5 X 10(5) units of recombinant human TNF produced a sustained disruption of the blood-aqueous barrier as manifested by elevated aqueous humor protein levels. In addition, 83% of rabbits receiving this dose of TNF developed hyperemia of limbal vessels and early neovascularization of the cornea. Many developed posterior synechiae (fibrous adhesions between the iris and the lens). TNF induced only a slight cellular response in the anterior chamber. Histologic studies confirmed the presence of new vessels and demonstrated a marked mononuclear infiltrate within and beneath the epithelium of the iris and ciliary body. Lower doses of TNF produced inconsistent results. Heating TNF completely destroyed its inflammatory effects. The time course of the ocular response to TNF and the quantity of recombinant protein needed to produce consistent effects were vastly different from effects observed with interleukin-1. For example, 24 hours after an intravitreal injection, 2.2 X 10(4) ng of TNF (5 X 10(5) units) produced significantly less protein extravasation and polymorphonuclear leukocyte infiltration than 4 ng of recombinant interleukin-1. Similarly, 24 hours after intravitreal injection, 1 ng of Escherichia coli endotoxin tended to be a more potent inflammatory stimulus than this quantity of TNF. These observations indicate that the ocular pathophysiologic effects of TNF can be readily distinguished from changes induced by either endotoxin or another endotoxin induced monokine, interleukin-1.